2003
DOI: 10.1038/sj.bjc.6600837
|View full text |Cite
|
Sign up to set email alerts
|

Pimonidazole binding in C6 rat brain glioma: relation with lipid droplet detection

Abstract: In C6 rat brain glioma, we have investigated the relation between hypoxia and the presence of lipid droplets in the cytoplasm of viable cells adjacent to necrosis. For this purpose, rats were stereotaxically implanted with C6 cells. Experiments were carried out by the end of the tumour development. A multifluorescence staining protocol combined with digital image analysis was used to quantitatively study the spatial distribution of hypoxic cells (pimonidazole), blood perfusion (Hoechst 33342), total vascular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 28 publications
(50 reference statements)
4
43
1
Order By: Relevance
“…A study on endothelial cells exposed to hypoxia showed an increase in lipid body formation to be dependent on O 2 concentration (26). It has also been shown in C6 rodent brain tumours that the presence of mobile lipids in viable cells is primarily associated with the highly hypoxic regions adjacent to necrotic areas (27). Hence, in non-necrotic biopsy samples, the positive correlation of total lipid droplets with cell density (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A study on endothelial cells exposed to hypoxia showed an increase in lipid body formation to be dependent on O 2 concentration (26). It has also been shown in C6 rodent brain tumours that the presence of mobile lipids in viable cells is primarily associated with the highly hypoxic regions adjacent to necrotic areas (27). Hence, in non-necrotic biopsy samples, the positive correlation of total lipid droplets with cell density (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…The wider range of droplet sizes that we observed compared with the C6 cell studies can be explained by tumour heterogeneity in vivo compared with cultured cells that are all in the same phase. It has also been observed in rodent C6 brain tumours that there is an increase in the number and size of droplets on going from the tumour periphery towards the central necrotic core (27).…”
Section: Discussionmentioning
confidence: 93%
“…LDs have long been recognized, based on light microscopy, to accumulate in hypoxic cells (Zoula et al, 2003), and studies have shown increased lipid metabolism in hypoxia (Laurenti et al, 2011;Mylonis et al, 2012;Shen et al, 2012). TGs contained in LDs are degraded to generate free FAs when cells need to produce ATP via b-oxidation, or to synthesize membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-induced LD accumulation is well studied and has been demonstrated under hypoxic conditions, irradiation and treatments with chemotherapeutic agents. [43][44][45][46] Recently, Gubern et al demonstrated that triglyceride synthesis and LD biogenesis during stress mainly takes place from pre-existing fatty acids and is dependent on group VI phospholipase A 2 (PLA 2 -VIA). 40 One possible explanation for LD accumulation is the impairment in mitochondrial fatty acid -oxidation, resulting from mitochondrial membrane damage, and leading to an increase in triglyceride storage.…”
Section: Discussionmentioning
confidence: 99%